2022
DOI: 10.1002/mame.202200262
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol–Metal Functionalized Hydrogel Dressing with Sustained Release, Antibacterial, and Antioxidant Properties for the Potential Treatment of Chronic Wounds

Abstract: Infection and chronic inflammation caused by oxidative stress are the main challenges in chronic wound healing. In this study, a silk fibroin/kappa‐carrageenan (kCA)‐based hydrogel functionalized with epigallocatechin‐3‐gallate (EGCG) and Cu2+ is fabricated for chronic wound healing. Polyphenol–metal functional complexes and ionic‐covalent entanglement networks are prepared by introducing Cu2+. Cu2+ coordinates with kCA to enhance the mechanical properties and chelates with EGCG to form an EGCG‐Cu2+ complex th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…The results suggested that the GS@EG–Cu–CA hydrogel had potential for killing the bacteria including MRSA around the wound tissues, indicating that the GS@EG–Cu–CA hydrogel has a significant broad-spectrum antibacterial effect. In fact, EGCG was believed to possess antimicrobial ability against various microorganisms; especially, the antimicrobial ability enhanced when the polyphenolic hydroxyl groups coordinate with metal cations to form a metal–polyphenolic complex. ,, As seen from Figure , the kill ratio of bacteria cultured in the GS@EG–Cu–CA hydrogel was significantly higher compared to that cultured in the GS@EG–Cu hydrogel. The reason was mainly attributed to the antibacterial activity EG–Cu–CA NPs that form a much steady metal–polyphenolic complex form.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results suggested that the GS@EG–Cu–CA hydrogel had potential for killing the bacteria including MRSA around the wound tissues, indicating that the GS@EG–Cu–CA hydrogel has a significant broad-spectrum antibacterial effect. In fact, EGCG was believed to possess antimicrobial ability against various microorganisms; especially, the antimicrobial ability enhanced when the polyphenolic hydroxyl groups coordinate with metal cations to form a metal–polyphenolic complex. ,, As seen from Figure , the kill ratio of bacteria cultured in the GS@EG–Cu–CA hydrogel was significantly higher compared to that cultured in the GS@EG–Cu hydrogel. The reason was mainly attributed to the antibacterial activity EG–Cu–CA NPs that form a much steady metal–polyphenolic complex form.…”
Section: Resultsmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA) is a common pathogenic and an impediment to cutaneous wound healing, and it is a great threat to public health due to the high associated morbidity and mortality . With the emergence of MRSA biofilms and persistent bacteria, it is urgent to find new ways to treat these infections besides antibiotics. , Previous reports have shown that (−)-epigallocatechin gallate (EGCG, one of the catechins) can inhibit the growth of bacteria and eliminate excessive reactive oxygen species (ROS). , Our recent results confirmed that introducing Cu 2+ into the fibroin-based hydrogel containing EGCG could elevate the antibacterial effect and exhibit great potential for the treatment of chronic wounds . Therefore, in this study, we have synthesized a thiolated gelatin/methacrylated silk fibroin (SF) hybrid hydrogel dressing (GS@EG–Cu–CA) incorporated with (−)-EGCG–copper ionic–kappa-carrageenan (κ-CA) nanoparticles (EG–Cu–CA NPs) by thio–ene click reaction (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 18 h of contact with the material containing TP at a concentration of 1 wt%, decreases in the viability of E. coli and S. aureus cells by approximately 99.92% and 100%, respectively, were observed. Zeng et al [ 125 ] produced a hydrogel with an immobilized complex made of Cu 2+ ions and the polyphenol found in the largest amounts in green tea: epigallocatechin-3-gallate (EGCG). The basis of the developed biomaterial for the treatment of chronic wounds was silk fibroin and kappa-carrageenan (kCA).…”
Section: Antimicrobial Biomaterialsmentioning
confidence: 99%
“…Hydrogels are "soft and wet" hydrophilic polymer materials containing abundant water inside their threedimensional network structures. 1,2 Because of similar characteristics to the extracellular matrix (ECM) of natural soft tissues, hydrogels have attracted considerable attention for their multifarious applications in biomedical areas such as tissue engineering, 3 drug delivery, 4 flexible sensors, [5][6][7] and soft robotics. 8 Particularly, with the rapid development progress of flexible electronic technology, hydrogel-based flexible electrodes and sensors have gained increasing attention in the application of human movement detection, wearable electronic devices and health monitoring.…”
Section: Introductionmentioning
confidence: 99%